QUALITE ET VITESSE D’ECRITURE MANUSCRITE DES ECOLIERS SOURDS-MUETS DE DEUXIEME ANNEE PRIMAIRE DU CENTRE ESPOIR DES SOURDS - ZOKO, Franck NGANGA; BENE-KABALA, Denis (IJRDO- Journal of Educational Research, 2021)
This research was conducted to ansuer the question of what can be the speed and quality of handwriting from deaf-mute schoolchildren at the hope center for the Deaf of Kisangani second grade primary class. It is known that this category of schoolchildren suffer from sensory deficiencies likely to handicap the acquisition of normal writing and in a suitable time. We collected the handwriting copies of these schoolchildren using the Bene-Kabala test sentence. To avoid being satisfied with the general impression reflected by these copies, we used quality scales and speed scales developed by Bene-Kabala. After the analyzes, we observed that the handwriting of these schoolchildren is poor both in terms of speed and in terms of writing quality.